A Statistical study of the crude Oil production function and its impact on the Iraqi GDP for the period (2005-2020) - Hayder Sabah Tuama; Ali Salman Tuama Alchaabawi (Periodica Journal, 2023)
The rentier problem in the Iraqi economy is hidden and still represents a double-edged sword at a time when it provides important financial resources, which can be a reason for achieving economic development and the locomotive of growth in the Iraqi economy. The Iraqi economy affected by the Dutch disease is the duality of the economy, the fragility of the commodity sectors and the dependence to a large extent on the oil sector, as fluctuations in crude oil prices lead to violent shocks in the economy. The research focused on formulating a statistical model to show the effect of independent factors on the gross domestic product, In particular, the variables emanating from the oil sector, and the relationship between the dependent variable and the independent explanatory variables was estimated.
Keywords: Crude Oil prices; Cointegration; Oil Exports; Gross Domestic Produc